Detection of Keto Synthase (KS) Gene Domain in Sponges and Bacterial Sponges - Atikana, Akhirta; Naim, Mohamad Azrul; Sipkema, Detmer (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2013)
Sponges are sources of various useful natural products. The natural compounds derived from sponges are mostly complex polyketide. The polyketide synthase genes (PKS) is responsible for the biosynthesis of complex polyketides. During this research, we detected ketosynthase (KS) gene domain from 10 species of marine sponges, collected from Mediterranean Sea (Aplysina aerophoba, Petrocia ficiformis, Axinella damicornis, Axinella veronicas, Crambe crambe) and North Sea (Halichondria panicea, Haliclona xena, Haliclona oculata, Suberites massa, Ephydatia fluviatilis). We also detected KS gene domain from 12 bacterial sponge isolated from H. panacea. We used a PCR-based approach to detect the ketosynthase (KS) gene domain of Polyketosynthase (PKS) genes. Our result showed that the sponges and the bacterial sponges are mostly KS-positive (700 bp). The presence of the PKS gene indicates the ability of the sponges to produce bioactive compound and potential natural product. The presence of the KS domain in both of the sponges and the bacterial sponges might also indicate that the bacterial sponges involved in the biosintesis of secondary metabolite of the sponges